An ethno-archaeological study of pottery vessels from the Saunyama territory in North-Eastern Zimbabwe - Nyamushosho, Robert Tendai (Midlands State University, 2014)
The Nyanga archaeological complex has been linked to a number of contemporary ethnic groups that include the Saunyama. These groups have been accredited to as the terrace builders of the complex but however this has been mostly perpetuated on the basis of incomplete archaeological inquiry and oral traditions. Such a scenario is the case of the Saunyama where archaeologists and historians have developed the archaeological identity of the Saunyama in relation to the Nyanga complex on the basis of incomplete archaeological enquiry and oral traditions hence their accounts remain hazy and fragmented. Surprisingly amongst other sources of ethnoarchaeology there is some evidence to confirm this link between the Saunyama and the hilltop settlements of Mt Muozi, an early phase of the Nyanga complex though this has not been proven. Given such a context in which Saunyama oral traditions have been given much precedence following the presence of ‘their’ sacred sites in this ancient cultural landscape. This study comes in with an attempt to develop a ceramic ethno-archaeological comparative study of archaeological complete pottery vessels situated at ‘their’ shrine of Muozi and ethnographic complete pottery vessels consumed by their descendants as one of the possibilities that could assist in verifying this link. This study portrays the prowess of ceramic ethno-archaeology in solving archaeological problems as it successfully confirms the link between the contemporary Saunyama and hilltop settlements of the Nyanga complex whereby stylistic and decoration attributes from both assemblages greatly show high levels of continuity from the archaeological record to the ethnographic present even though some changes are notable. The study also crafts the humanistic side of the story that had lacked in most archaeological texts as concluded by Beach (1980).